Research and integrated coastal zone management in rapidly developing estuarine harbours: A review to inform sustainment of functions in Jiaozhou Bay, China. (November 2015) - Liang, Sheng-kang; Pearson, Stuart; Wu, Wen; Ma, Ying-jie; Qiao, Lu-lu; Wang, Xiao Hua; Li, Jing-mei; Wang, Xiu-lin
Abstract: China's Jiaozhou Bay is an important example of integrated coastal zone management because it has received scientific and management attention and becomes useful to other coastal managers and researchers experiencing similar challenges. Water research shows that the condition of the environment is dominated by overwhelming nutrient flows and land reclamation that has reduced the ecosystem's ability to sustain itself. Interventions have included a raft of legal measures, restocking and mariculture of all commercial species, phasing out of commercial fisheries, increasing treatment of waste water, and recently, establishing total discharge controls. Past investigations into the use of market-based solutions and further integration using management models are included in this paper. Suggested improvements are based on consensus of multiple authors with different backgrounds that the situation is serious and the trends are alarming. The suggestions include careful reexamination of the business as usual approach, new research and management approaches that exploit the advantages of multiple perspectives and collaboration. This integration demands new ways of using plans, standards, indicators, monitoring and knowledge more generally. At the foundation is the information about the environment and management actions to ensure that new management approaches, including eco-compensation, are carefully planned and monitored. Integrated water research planned by various agencies will develop these ideas into actionable knowledge on one of the world's most rapidly developing coastlines. The experience of water research and management in this rapidly developing coastline is, and will be, globally significant. This paper provides an important insight into knowing the research challenges for estuary harbours in rapidly developing areas. Graphical abstract: Highlights: Jiaozhou Bay's water and environmental systems are on a downward trajectory. Intense development pressures and inadequate responses are to blame. Coping systems have been exceeded. Existing indicators need to be used to drive private and public agency improvements. Further integration of water research and management is needed.